ANALISIS TINGKAT KEPUASAN PENGGUNA APLIKASI "ALPUKAT BETAWI" DALAM MENGAKSES LAYANAN KEPENDUDUKAN DAN PENCATATAN SIPIL DI KELURAHAN SUKAPURA JAKARTA UTARA - Ananda Tania Putri (2022)
This study aims to discuss and analyze the effect of fast and easy access to population and civil registration services on the level of satisfaction of users of the "Alpukat Betawi" application using the theory of public services, quality of public services, and user satisfaction. The type of research used is quantitative research with descriptive methods using primary data sources and secondary data sources. The sampling technique used is probability sampling, namely simple random sampling. Researchers used data analysis techniques, namely descriptive statistics, simple linear regression, normality test, autocorrelation test, t test (partial), f test (simultaneous), validity test and reliability test. The results showed that the value of the Service Access variable had a positive effect on User Satisfaction with the "Alpukat Betawi" application in kelurahan Sukapura. This is evidenced by the statistical test results for the Service Access variable which show the t-count value is greater than t-table and the significance value is smaller. This means that the Service Access variable has a positive and significant effect on the interest in user. So that the higher the level of Service Access it will encourage User Satisfaction. This shows that Service Access will increase User Satisfaction. Keywords: Service access, user satisfaction, public services, quality of public services.